A new perspectives on breastfeeding practice reconstruction in bioarchaeology – an oxygen isotopes study in an animal model - Lisowska-Gaczorek, Aleksandra; Cienkosz-Stepańczak, Beata; Furmanek, Mirosław; Szostek, Krzysztof (Anthropological Review, 2023)
Research using stable isotopes for the reconstruction of breastfeeding strategies are based on assumptions that have not yet been verified by experimental studies. Interpreting the results of isotope analysis is associated with a certain degree of uncertainty, mainly due to the lack of information on how isotopes are distributed in mothers, breast-fed and weaned offspring. Culinary practices also can affect the interpretation of isotope results. Considering positive correlation between oxygen isotope composition of drinking water and bone phosphates, experimental studies were carried out using rats as an animal model. The experiment showed that apatites of breast-fed offspring were enriched 1.6‰ in comparison to the values observed in their mothers. In the boiled water model, the difference was 1.8‰. On the basis of the animal model, it was estimated that the difference in 18O between mother and child in the human species may amount to approximately 2.7‰, and long-term intake of boiled liquid food and beverages will not compensate the difference. The experiment allowed observation of the effect of changes in isotope ratios to a change in trophic levels during breastfeeding and weaning, as well as the additional effect associated with the consumption of isotope enriched water during thermal treatment.